I want you back - James, Lorelei (James, Lorelei. Want you series., 2019)
Former NHL star Jaxson Lund has returned to the Twin Cities, but he's at loose ends, unsure if he belongs at Lund Industries, or where he stands with Lucy, his ex-girlfriend and mother of his daughter, Mimi. Despite the signs she'd like to leave him in the penalty box, the attraction burning between them reinforces his determination to prove that he deserves a second chance... Lucy Quade is in a good place with a steady job, a nice apartment, and a well-adjusted daughter, which is why she's hesitant when Jax insists on co-parenting. It's not that Lucy doesn't trust Jax...she's just unconvinced he can handle multiple responsibilities when he's been singularly focused on playing hockey. But when issues arise with Mimi, Lucy's shocked at how levelheaded and paternal he acts, giving her a glimpse of the Jax she used to know, the sexy, sweet man she fell for years ago. Once Lucy lets her guard down, Jax goes all in to show her how good they are together, but will their past remain too large an obstacle to ever overcome?